The extensive margin of trade and monetary policy - Yuko Imura; Malik Shukayev (Bank of Canada, 2018)
This paper studies the effects of monetary policy shocks on firms' participation in exporting. We develop a two-country dynamic stochastic general equilibrium model in which heterogeneous firms make forward-looking decisions on whether to participate in the export market and prices are staggered across firms and time. We show that while lower interest rates and a currency depreciation associated with an expansionary monetary policy help to increase the value of exporting, the inflationary effects of the policy stimulus weaken the competitiveness of some firms, resulting in a contraction in firms' export participation. In contrast, positive productivity shocks lead to a currency depreciation and an expansion in export participation at the same time. We show that, overall, the extensive margin is more sensitive to firms' price competitiveness with other firms in the export market than to exchange rate movements or interest rates.
Keywords: F44; E52; F12; 330; Business fluctuations and cycles; Economic models; Firm dynamics; International topics; Monetary policy